The Accounting Principles and Financial Reporting Rules in Polish and Spanish Regulations - Burchart, Renata; Monteys, Ramon Soldevila (Olsztyn Economic Journal, 2017)
The purpose of the research was to identify differences and similarities in the basic provisions of Polish and Spanish legal acts regulating the accounting principles, elements of reporting and conditions of examination and publication of financial statements of entities. The Polish Accounting Act lists eight overarching accounting policies, while the Spanish General Accounting Plan describes the same content, however, contained in only six principles.In both countries there are three main elements of the financial statement: Balance Sheet, Income Statement and Additional Information, for all companies with full accounting, and two additional items: Cash flow and Statement of changes in equity for entities whose reports are subject to mandatory examination and disclosure. The obligation to audit accounts for entities that meet two of the three conditions are the same in both countries, but the total balance sheet value and sales revenue in the preceding year, expressed in euros, in Spain are 12,3% higher than in Poland.